Chitosan hydrogel/3D-printed poly(ε‐caprolactone) hybrid scaffold containing synovial mesenchymal stem cells for cartilage regeneration based on tetrahedral framework nucleic acid recruitment. (November 2021) - Li, Pinxue; Fu, Liwei; Liao, Zhiyao; Peng, Yu; Ning, Chao; Gao, Cangjian; Zhang, Daxu; Sui, Xiang; Lin, Yunfeng; Liu, Shuyun; Hao, Chunxiang; Guo, Quanyi
Abstract: Articular cartilage (AC) injury repair has always been a difficult problem for clinicians and researchers. Recently, a promising therapy based on mesenchymal stem cells (MSCs) has been developed for the regeneration of cartilage defects. As endogenous articular stem cells, synovial MSCs (SMSCs) possess strong chondrogenic differentiation ability and articular specificity. In this study, a cartilage regenerative system was developed based on a chitosan (CS) hydrogel/3D-printed poly(ε‐caprolactone) (PCL) hybrid containing SMSCs and recruiting tetrahedral framework nucleic acid (TFNA) injected into the articular cavity. TFNA, which is a promising DNA nanomaterial for improving the regenerative microenvironment, could be taken up into SMSCs and promoted the proliferation and chondrogenic differentiation of SMSCs. CS, as a cationic polysaccharide, can bind to DNA through electrostatic action and recruit free TFNA after articular cavity injection in vivo. The 3D-printed PCL scaffold provided basic mechanical support, and TFNA provided a good microenvironment for the proliferation and chondrogenic differentiation of the delivered SMSCs and promoted cartilage regeneration, thus greatly improving the repair of cartilage defects. In conclusion, this study confirmed that a CS hydrogel/3D-printed PCL hybrid scaffold containing SMSCs could be a promising strategy for cartilage regeneration based on chitosan-directed TFNA recruitment and TFNA-enhanced cell proliferation and chondrogenesis.